1995
DOI: 10.1083/jcb.131.6.1547
|View full text |Cite
|
Sign up to set email alerts
|

An amino-terminal extension is required for the secretion of chick agrin and its binding to extracellular matrix.

Abstract: Abstract. Agrin is an extracellular matrix (ECM) protein with a calculated relative molecular mass of more than 200 kD that induces the aggregation of acetylcholine receptors (AChRs) at the neuromuscular junction. This activity has been mapped to its COOH terminus. In an attempt to identify the functions of the NH2-terminal end, we have now characterized full-length chick agrin. We show that chick agrin encoded by a previously described cDNA is not secreted from transfected cells. Secretion is achieved with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
144
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(156 citation statements)
references
References 71 publications
(157 reference statements)
12
144
0
Order By: Relevance
“…Consistent with this hypothesis, bath-applied agrin induces in cultured myotubes the accumulation of AChRs and other molecules associated with normal NMJs (Wallace, 1989), and, in mice carrying a mutated agrin gene, muscle fibers fail to form functional endplates (Gautam et al, 1996). Agrin is characterized by alternatively spliced sites, termed A and B ( y and z in rat agrin; Rupp et al, 1992) at the C-terminal end and, in the chick, the NtA domain at the N-terminal part (Ruegg et al, 1992;Denzer et al, 1995). In vitro, the most potent AChRaggregating isoform of agrin is expressed by motor neurons and contains a four amino acid insert at the A splice site and an eight amino acid insert at the B splice site.…”
mentioning
confidence: 76%
“…Consistent with this hypothesis, bath-applied agrin induces in cultured myotubes the accumulation of AChRs and other molecules associated with normal NMJs (Wallace, 1989), and, in mice carrying a mutated agrin gene, muscle fibers fail to form functional endplates (Gautam et al, 1996). Agrin is characterized by alternatively spliced sites, termed A and B ( y and z in rat agrin; Rupp et al, 1992) at the C-terminal end and, in the chick, the NtA domain at the N-terminal part (Ruegg et al, 1992;Denzer et al, 1995). In vitro, the most potent AChRaggregating isoform of agrin is expressed by motor neurons and contains a four amino acid insert at the A splice site and an eight amino acid insert at the B splice site.…”
mentioning
confidence: 76%
“…1). In chick agrin, one site is located near the N-terminus (Tsen et al 1995a;Denzer et al 1995), and two sites (called A and B), are located within the C-terminus . The corresponding conserved C-terminal splice sites in rat are called y and z (Ferns et al 1992).…”
Section: Postsynaptic Differentiationmentioning
confidence: 99%
“…In addition, the splice sites, the serine/threonine rich regions (S/T), potential N-linked glycosylation sites, and conserved glycosaminoglycan (GAG) chain attachment sites are indicated. Heparan sulfate GAG side chains and other carbohydrates attached to the 225-kDa-core protein have been shown to be the reason for the high apparent Mr of 400±600 kDa of agrin on SDS polyacrylamide gel electrophoresis (Tsen et al 1995b;Denzer et al 1995). Shaded rectangles represent the fragments sufficient for the binding to laminin, to a-dystroglycan, and to the not yet identified signaling receptor of agrin specific binding to a signaling receptor on the muscle cell membrane.…”
Section: Mechanism Of Agrin-mediated Achr Aggregationmentioning
confidence: 99%
“…Plasmids-Plasmid MC1061/P3 (Invitrogen) containing full-length chick agrin cDNA (14) was used as a template to generate the different agrin peptide fragments. The following primers were used: PF1, 5Ј-G-TCAGCTAGC(T)AACTGCCCCGAACGGGA-3Ј (sense) and 5Ј-TTCTT-CTTCAGCGGCCGCGTACTGAGGGGCTGGGTTGA-3Ј (antisense); PF2, 5Ј-GTCAGCTAGC(T)ATGTGGCCTGCCCACCGCAA-3Ј (sense) and 5Ј-TTCTTCTTCAGCGGCCGCGGTGAGGCCATCGGTGCCACA-3Ј (antisense); PF3, 5Ј-GTCAGCTAGC(T)CAGTGCGTGTGTCCCCGCTG-T-3Ј (sense) and 5Ј-TTCTTCTTCAGCGGCCGCGCTCCCTTCTGCATC-AGCA-3Ј (antisense); PF4, 5Ј-GTCAGCTAGC(T)AACTGTCCGGCTAC-CAAAGTC-3Ј (sense) and 5Ј-TTCTTCTTCAGCGGCCGCGGCCAGGT-AGGACTTGCCA-3Ј (antisense); PF5, 5Ј-GTCAGCTAGC(T)AACTGCC-CCGAACGGGA-3Ј (sense) and 5Ј-TTCTTCTTCAGCGGCCGCCACCT-CTGCACAGGGGT-3Ј (antisense); PF6, 5Ј-GTCAGCTAGC(T)AAGGA-CCCCTGTGCAGAGGTG-3Ј (sense) and 5Ј-TTCTTCTTCAGCGGCCG-CCTGACTGCAGTGCACAACTGG-3Ј (antisense); PF7, 5Ј-GTCAGCTA-GC(T)CCAGTTGTGCACTGCAGTCAG-3Ј (sense) and 5Ј-TTCTTCTTC-AGCGGCCGCGCTCCCTTCTGCATCAGCA-3Ј (antisense); PF8, 5Ј-GT-CAGCTAGC(T)AACTGCCCCGAACGGGA-3Ј (sense) and 5Ј-TTCTTC-TTCAGCGGCCGCGGAGGCTTGGGAGGGGT-3Ј (antisense); and PF9, 5Ј-GTCAGCTAGC(T)TCCCAAGCCTCCTGTGTCTGC-3Ј (sense) and 5Ј-TTCTTCTTCAGCGGCCGCCTGACTGCAGTGCACAACTGG-3Ј (antisense).…”
Section: Methodsmentioning
confidence: 99%
“…Third, the GAG glycosylated peptides should bind to anion exchange beads and elute only at ionic strength equal to or higher than 1 M NaCl. We concentrated our efforts on agrin segments from the N terminus to the first laminin G-like domain because previous studies have already shown that the C-terminal laminin G-like domains of agrin are not GAG glycosylated (14). A diagram of agrin with its different domains is shown in Fig.…”
Section: Expression Of N-terminal Agrin Fragments-mentioning
confidence: 99%